Combined Inoculation with Multiple Arbuscular Mycorrhizal Fungi Improves Growth, Nutrient Uptake and Photosynthesis in Cucumber Seedlings - Chen, Shuangchen; Zhao, Hongjiao; Zou, Chenchen; Li, Yongsheng; Chen, Yifei; Wang, Zhonghong; Jiang, Yan; Liu, Airong; Zhao, Puyan; Wang, Mengmeng; Ahammed, Golam J. (Frontiers in Microbiology, 2017)
Mycorrhizal inoculation stimulates growth, photosynthesis and nutrient uptake in a wide range of host plants. However, the ultimate effects of arbuscular mycorrhyzal (AM) symbiosis vary with the plants and fungal species involved in the association. Therefore, identification of the appropriate combinations of AM fungi (AMF) that interact synergistically to improve their benefits is of high significance. Here, three AM fungal compositions namely VT (Claroideoglomus sp., Funneliformis sp., Diversispora sp., Glomus sp. and Rhizophagus sp.) and BF (G. intradices, G. microageregatum BEG and G. Claroideum BEG 210), and Funneliformis mosseae (Fm) were investigated with respect to the growth, gas exchange parameters, enzymes activities in Calvin cycles and related gene expression in cucumber seedlings. The results showed that VT, BF and Fm could successfully colonize cucumber root to a different degree with the colonization rates 82.38%, 74.65% and 70.32% at 46 d post inoculation, respectively. The plant height, stem diameter, dry weight, root to shoot ratio of cucumber seedlings inoculated with AMF increased significantly compared with the non-inoculated control. Moreover, AMF colonization greatly increased the root activity, chlorophyll content, net photosynthetic rate, light saturated rate of the CO2 assimilation (Asat), maximum carboxylation rates (Vcmax) and maximum ribulose-1,5-bis-phosphate (RuBP) regeneration rate (Jmax), which were increased by 52.81%, 30.75%, 58.76%, 47.00%, 69.15% and 65.53% when inoculated with VT, respectively. The activities of some key enzymes such RuBP carboxylase/oxygenase (RuBisCO), D-fructose-1,6-bisphosphatase (FBPase), D-fructose-6-phosphatase (F6P) and ribulose-5-phosphate kinase (Ru5PK), and related gene expression involved in the Calvin cycle including RCA, FBPase, FBPA, SBPase, rbcS and rbcL were upregulated by AMF colonization. AMF inoculation also improved macro- and micro nutrient contents such as N, P, K, S, Ca, Cu, Fe, Mn, Mg and Zn in roots. Further analysis revealed that inoculation with VT had relatively better effect on growth of cucumber seedling followed by BF and Fm, indicating that AMF composition consisting of distant AMF species may have a better effect than a single or closely related AMF spp. This study advances the understanding of plant responses to different AM fungi towards development of strategies on AMF-promoted vegetable production.